2016
DOI: 10.1177/1753465816632638
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to the management of noneosinophilic asthma

Abstract: Noneosinophilic airway inflammation occurs in approximately 50% of patients with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 213 publications
0
91
0
1
Order By: Relevance
“…This disease has been traditionally associated with the type 2 cytokines IL-4, IL-5, and IL-13, which promote immunoglobulin class switching to IgE, eosinophilia, and AHR, respectively (2,3). However, approximately half of patients with asthma have a noneosinophilic form of this disease, many with predominantly neutrophilic inflammation of the airway (4,5). Unfortunately, these patients respond very poorly to inhaled corticosteroids, the gold standard asthma therapy (6), and there is a need for novel therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…This disease has been traditionally associated with the type 2 cytokines IL-4, IL-5, and IL-13, which promote immunoglobulin class switching to IgE, eosinophilia, and AHR, respectively (2,3). However, approximately half of patients with asthma have a noneosinophilic form of this disease, many with predominantly neutrophilic inflammation of the airway (4,5). Unfortunately, these patients respond very poorly to inhaled corticosteroids, the gold standard asthma therapy (6), and there is a need for novel therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, no other drug, especially no biologic, is known to target this asthma phenotype. The results of clinical trials of biologics targeting mediators associated with non‐eosinophilic inflammation, such as IL‐17 and tumor necrosis factor (TNF)‐α, are disappointing …”
Section: Other Biologics Which Could Be Of Interest In Children With mentioning
confidence: 99%
“…Neutrophilic airway inflammation is found in some patients with asthma although the role of neutrophils in the pathogenesis of asthma is uncertain 58 . A phase II study found that the 4-weeks treatment with CXCR2 antagonist SCH527123 reduced sputum neutrophil percentage by 36.3% in patients with severe asthma and sputum neutrophils > 40%.…”
Section: Cxcr2 Antagonistsmentioning
confidence: 99%